Description of Comprehension, Perceptions, and Challenges of Science Teachers' Formative Assessment Practice in Wonosobo - Ismun Nisa Nadhifah; Agista Sintia Dewi Adila; Ayu Lestari (PendIPA Journal of Science Education, 2023)
Many studies have demonstrated the effectiveness of formative science assessments, which were utilized in education in many industrialized nations as recently as two decades ago. The adoption of formative assessment procedures in Indonesia has, however, fallen short of expectations due to a number of factors, including the teachers' lack of understanding, preconceptions, and various challenges. Using an exploratory descriptive qualitative methodology, this study aimed to establish how teachers understand and perceive formative assessment, as well as the various implementation issues they experience in the classroom. Chi-square analysis was utilized to determine the correlations between the ordinal variables. The data were gathered through an online survey followed by interviews with five teachers possessing various profiles. It was determined that teachers' conceptual understanding and perceptions of formative assessment fell into the "fairly good" category, demonstrating that they had a clear understanding of the concept and favorable perceptions of it. There was significant evidence of the relationship between training and comprehension and between comprehension and the frequency of applying formative assessments in science learning. However, the teachers admitted that they had not regularly used formative assessments in the classroom. The biggest challenges, according to teachers, were too many students, a lack of time, a lack of practical knowledge, and insufficient or inappropriate training.